Deimination Protein Profiles in Alligator mississippiensis Reveal Plasma and Extracellular Vesicle-Specific Signatures Relating to Immunity, Metabolic Function, and Gene Regulation - Criscitiello, Michael F.; Kraev, Igor; Petersen, Lene H.; Lange, Sigrun (Frontiers in Immunology, 2020)
Alligators are crocodilians and among few species which endured the Cretaceous–Paleogene extinction event. With long life spans, low metabolic rates, unusual immunological characteristics and cancer resistance, crocodilians may hold information for molecular pathways underlying such physiological traits. Peptidylarginine deiminases (PADs) are a group of calcium-activated enzymes that cause post-translational protein deimination/citrullination in a range of target proteins contributing to protein moonlighting functions in health and disease. PADs are phylogenetically conserved and are also a key regulator of extracellular vesicle (EV) release; a critical part of cellular communication. As little is known about PAD-mediated mechanisms in reptile immunology, this study was aimed at profiling EVs and protein deimination in Alligator mississippiensis. Alligator plasma-EVs were found to be poly-dispersed in a 50-400 nm size range. Key immune, metabolic and gene regulatory proteins were identified to be post-translationally deiminated in plasma and plasma-EVs, with some overlapping hits, while some were unique to either plasma or plasma-EVs. In whole plasma, 112 target proteins were identified to be deiminated, while 77 proteins were found as deiminated protein hits in plasma-EVs, whereof 31 were specific for EVs only, including proteins specific for gene regulatory functions (e.g. histones). GO and KEGG enrichment analysis revealed KEGG pathways specific to deiminated proteins in whole plasma related to adipocytokine signalling, while KEGG pathways of deiminated proteins specific to EVs included ribosome, biosynthesis of amino acids and glycolysis/gluconeogenesis pathways as well as core histones. This highlights roles for EV-mediated export of deiminated protein cargo with roles in metabolism and gene regulation, also related to cancer. The identification of post-translational deimination and EV-mediated communication in alligator plasma revealed here, contributes to current understanding of protein moonlighting functions and EV-mediated communication in these ancient reptiles, providing novel insight into their unusual immune systems and physiological traits. In addition our findings may shed light on pathways underlying cancer-resistance and anti-bacterial resistance, with translatable value to human pathologies.